Ayurvedic preparations for the treatment of iron deficiency anemia: A short review - Amit Agrawal; Raghi Raveendran; Sanjana Baranwal (Indian Journal of Integrative Medicine, 2022)
Iron deficiency is one of the most common causes of anemia. The main etiologies of iron deficiency were blood loss due to menstruation and due to gastrointestinal bleeding. Beyond anemia, lack of iron has protean manifestations such as fatigue, hair loss, and restless legs. Serum ferritin is the most efficient test for the diagnosis of iron deficiency anemia (IDA). Iron replacement can be done orally or contraindicated with intravenous iron. This study was designed to describe the IDA in patient populations of different age groups, its impact during pregnancy, and the general population. In this review, we demonstrated the causes, symptoms, prevention, and treatments of IDA. We conducted the study using the electronic databases PubMed, Google Scholar, the selection of research papers was restricted to the English language and humans. Research papers were included published from 2000 to 2021 for this review. The different types of formulation mainly Lauha bhasma are used for patient populations of different age groups (infant, elderly), pregnant women, and general patient populations, which were described well in this review. This review aims to acknowledge the ayurvedic medications for IDA in different patient populations.